Life-history traits of the freshwater garfish xenentodon cancila (Hamilton 1822) (Belonidae) in the Ganges River, Northwestern Bangladesh - Hossain, Md. Yeamin; Sayed Jewel, Md. Abu; Rahman, Md. Mosaddequr; Haque, A.B.M. Mohidul; M. ElBaghdady, Heba Allah; Ohtomi, Jun (Universiti Kebangsaan Malaysia, 2013)
The freshwater garfish, Xenentodon cancila (Hamilton 1822), is one of the commercially important, nutritionally valuable food fish in Asian countries, but the natural populations are seriously decreasing due to high fishing pressure and other factors. This study describes the life history traits, including sex ratio (SR), length-frequency distributions (LFDs), length-weight relationships (LWRs), length-length relationships (LLRs), condition factors (Allometric, KA; Fulton’s, KF; relative condition, KR; relative weight, WR) and form factor (a3.0) of X. cancila in the Ganges (Padma) River, northwestern Bangladesh. A total of 175 specimens ranging from 10.50-21.00 cm TL (total length) and 1.44-20.67 g BW (body weight) were investigated in this study. Sampling was done using traditional fishing gears from April 2011 to March 2012. The overall sex ratio showed no significant differences from the expected value of 1:1 (df = 1, χ2 = 0.28, p<0.05), whereas significant difference was found in the LFD (TL) between the sexes (Two tailed, p<0.001). The allometric coefficient b for the LWR indicated positive allometric growth in males, females and combined sexes. The results further indicated that the LLRs were highly correlated. Both KR and KF showed significant variations (Two tailed, p<0.001) between male and female. Also, WR was significantly different from 100 for both sexes (p<0.01), indicating the imbalance habitat with food availability relative to the presence of predators for X. cancila. The calculated values of a3.0 were as 0.0304, 0.0268 and 0.0252 for males, females and combined sexes of X. cancila. This study reports the first complete and comprehensive description of life-history traits for X. cancila from Bangladeshi waters. The data should be useful for the sustainable conservation of this critically endangered fishery in Bangladesh and neighboring countries.